Corrosion-resistant 5G communication cable and production method thereof

By using corrosion inhibitors and high-strength material layers in 5G communication cables, the corrosion problem of cables in harsh environments is solved, corrosion resistance and mechanical strength are improved, service life is extended and maintenance costs are reduced.

CN119132718APending Publication Date: 2024-12-13SHAOXING LIBO CABLE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411237444.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Common communication cables are prone to corrosion and aging in harsh environments, affecting their service life, especially in outdoor application scenarios such as 5G communication base stations, resulting in frequent damage and replacement, increasing maintenance costs.

Method used

Using corrosion-resistant 5G communication cable design, including copper core, insulating material layers of polyethylene and carbon black, as well as sheathing material layers of carboxylic acrylic resin, SAN resin and anti-corrosion additives, through multiple stretching and extrusion Extrusion, braiding and coating processes to improve the corrosion resistance and mechanical strength of the cable.

Benefits of technology

It significantly improves the corrosion resistance and mechanical strength of the cable, extends the service life, reduces damage and replacement frequency caused by environmental corrosion, reduces maintenance costs, and ensures the stable operation of the 5G communication network.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a corrosion-resistant 5G communication cable and a production method thereof. According to the anti-corrosion cable, the anti-corrosion additive is added into the cable sheath material layer, so that the corrosion resistance of the cable is remarkably improved. The preparation process of the anti-corrosion additive comprises the following steps: mixing carboxyl acrylic resin with nano tin dioxide powder, adding a silane coupling agent KH-570, stirring for a long time, carrying out ultrasonic treatment, and mixing with various inorganic fillers to finally obtain the additive with excellent corrosion resistance. With the application of the auxiliary agent, the cable can resist corrosion of environmental factors such as acid, alkali, salt mist and moisture, so that the service life of the cable is prolonged. The corrosion resistance is particularly important in outdoor application scenes such as 5G communication base stations, and cable damage and replacement frequency caused by environmental corrosion can be reduced, so that the maintenance cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of communication cables, and specifically relates to a corrosion-resistant 5G communication cable and a production method thereof. Background Art

[0002] 5G communication cable, as an important part of the new generation of mobile communication technology, undertakes the key mission of transmitting high-speed data and realizing the interconnection of all things. 5G communication cable, designed specifically for 5G network, has the characteristics of high speed, low latency and large capacity. It adopts advanced materials and processes to meet the stringent requirements of 5G communication system for transmission rate, bandwidth and reliability. 5G communication cable mainly includes coaxial cable, optical fiber cable and leaky cable to meet the application needs in different scenarios. 5G communication cable is widely used, mainly including the following aspects: infrastructure construction: used for the connection of 5G base stations, antennas, data centers and other facilities; smart home: to achieve rapid interconnection of various smart devices in the home; industrial Internet: to support real-time monitoring and control of equipment in the factory; Internet of Vehicles: to provide high-speed and stable communication guarantee for autonomous driving, intelligent transportation, etc. In short, as the infrastructure for 5G network construction, the performance and quality of 5G communication cable are directly related to the operation effect of the entire network. With the continuous development and popularization of 5G technology, 5G communication cable will inject strong impetus into the development of my country's digital economy and society.

[0003] However, common communication cables are not treated with corrosion protection. When used in harsh environments, they may corrode and age, thus affecting the service life of the entire cable. Summary of the invention

[0004] The purpose of the present invention is to provide a corrosion-resistant 5G communication cable and a production method thereof in order to solve the above-mentioned problems.

[0005] The technical solution adopted by the present invention is as follows: a corrosion-resistant 5G communication cable, the 5G communication cable comprising: a cable conductor, an insulating material layer and a cable sheath material layer;

[0006] The cable conductor is a copper core;

[0007] The insulating material layer comprises 200 to 400 parts by weight of polyethylene, 25 to 35 parts by weight of antioxidant and 15 to 25 parts by weight of carbon black;

[0008] The cable sheath material layer comprises 600-800 parts by weight of carboxyl acrylic resin, 200-400 parts by weight of SAN resin, 25-35 parts by weight of anticorrosion additive, 2-5 parts by weight of lubricant, 10-20 parts by weight of foaming agent, 10-18 parts by weight of organic antimony stabilizer, 20-30 parts by weight of flame retardant, 10-20 parts by weight of reinforcing modifier and 20-25 parts by weight of anti-aging agent.

[0009] In a preferred embodiment, the production method comprises the following steps:

[0010] S1: First, prepare the raw materials for preparing the corrosion-resistant 5G communication cable, and weigh: 200-400 parts by weight of polyethylene, 25-35 parts by weight of antioxidant, and 15-25 parts by weight of carbon black;

[0011] 600-800 parts by weight of carboxyl acrylic resin, 200-400 parts by weight of SAN resin, 25-35 parts by weight of anticorrosion additive, 2-5 parts by weight of lubricant, 10-20 parts by weight of foaming agent, 10-18 parts by weight of organic antimony stabilizer, 20-30 parts by weight of flame retardant, 10-20 parts by weight of reinforcing modifier and 20-25 parts by weight of anti-aging agent;

[0012] S2: The copper core is stretched through a wire drawing machine in multiple passes to reach the required conductor diameter, and then the conductor is twisted to improve the flexibility and tensile strength of the conductor;

[0013] S3: adding the polyethylene, antioxidant and carbon black pellets weighed in step S1 into an extruder, and extruding them into a cable insulation layer after high temperature melting;

[0014] S4: Cooling the insulation layer, cooling the extruded insulation layer through a cooling water tank to ensure uniform thickness of the insulation layer;

[0015] S5: preparing a cable sheath material layer, adding polypropylene (PP) or polytetrafluoroethylene (PTFE) pellets into an extruder, and extruding them into a cable sheath layer after high-temperature melting;

[0016] S6: Cooling the jacket layer, cooling the extruded jacket layer through a cooling water tank to ensure uniform jacket layer thickness;

[0017] S7: Twisting the insulated conductors in a certain order to form a cable core;

[0018] S8: The cable core is braided outside to increase the mechanical strength and tensile strength of the cable;

[0019] S9: The braided cable core is coated with a sheath material through a coating machine to form a complete cable;

[0020] S 10: Cable performance testing, including voltage resistance testing, insulation resistance testing, aging testing, etc. of finished cables to ensure that the cable performance meets the requirements of 5G communications

[0021] S11: The cables are then collected, stored and packaged, completing the entire production process of the corrosion-resistant 5G communication cable.

[0022] In a preferred embodiment, in step S1, the method of the anti-corrosion additive is as follows: first, take carboxyl acrylic resin and nano tin dioxide powder and mix them to a uniform state. Then, add silane coupling agent KH-570 and stir for 20 to 28 hours at 38 to 46 degrees Celsius. After stirring, cool it to room temperature and transfer it to an ice water bath for crushing. Then, perform ultrasonic treatment for 10 to 14 minutes to obtain material a.

[0023] Next, prepare an acidic composite intercalation aqueous solution, that is, disperse concentrated sulfuric acid evenly in distilled water. At the same time, place the montmorillonite in a calcining furnace and calcine it at a temperature of 750 to 850 degrees Celsius for 1 to 5 hours, followed by cooling. Soak the calcined montmorillonite in a hydrochloric acid solution for 2 to 4 hours, filter, wash and dry it, and crush it into a powder of 150 to 350 mesh. Add this powder to the acidic composite intercalation aqueous solution prepared previously, mix well, and heat the mixture to 85 to 95 degrees Celsius, and keep it warm for 1 to 3 hours.

[0024] Subsequently, material a, calcium sulfate, silicon nitride, montmorillonite powder, barium sulfate, antimony trioxide, weathered coal, seaweed powder, zinc phosphate, bentonite, zeolite powder and zirconium oxide are added to the mixture and mixed thoroughly. In a water bath of 45 to 55 degrees Celsius, ultrasonic-mechanical stirring is used to disperse for 2 to 4 hours. After standing and stratifying, the upper clear liquid is discarded, the lower reaction product is filtered and washed, and vacuum dried at 750 to 850 degrees Celsius until constant weight. The dried product is ground and screened through a 150 to 250 mesh sieve to obtain an antiseptic additive raw material A.

[0025] Finally, 10% of the total weight of nano camphor leaf fiber powder is added to the anti-corrosion agent raw material A, and the mixture is evenly mixed to obtain the final anti-corrosion agent.

[0026] In a preferred embodiment, in step S1, the foaming agent is azodicarbonamide.

[0027] In a preferred embodiment, in step S1, the flame retardant is a mixture of resorcinol bis(diphenyl phosphate), bisphenol A bis(diphenyl phosphate), tributyl tin oxide, glass fiber powder, activated clay, and aluminum hydroxide, and the mixing ratio is: resorcinol bis(diphenyl phosphate): bisphenol A bis(diphenyl phosphate): tributyl tin oxide: molybdenum hydroxide: activated clay: aluminum hydroxide = 1:2:1:1:1:3;

[0028] The anti-aging agent is one or more of tea polyphenols, phytic acid, phenolic antioxidant 1076, antioxidant 1010 or phosphite antioxidant 168.

[0029] In a preferred embodiment, in step S1, the reinforcing modifier is a mixture of ethylene-butyl acrylate-glycidyl methacrylate terpolymer and ethylene-vinyl acetate copolymer in a weight ratio of 1-5:1-5;

[0030] The lubricant is one of calcium stearate, barium stearate, magnesium stearate and polyethylene glycol.

[0031] In a preferred embodiment, in step S8, first, the insulated conductor core is placed on a braiding machine, and a suitable braiding angle and braiding density are selected according to the design requirements of the cable. The braiding angle is usually set between 45° and 90° to balance the softness and strength of the cable. The braiding density is determined according to the use environment of the cable, and generally the number of braided wires per meter length is selected between 10 and 30. During the braiding process, it is necessary to ensure that the braided layer is close to the conductor core without looseness and blistering. The braiding material usually selects high-strength, corrosion-resistant metal or synthetic fiber. The braiding speed should be adjusted according to the material properties and equipment performance to maintain the stability and efficiency of the braiding process. During the entire braiding process, the operator needs to regularly check the braiding quality to ensure the uniformity and integrity of the cable braiding layer.

[0032] In a preferred embodiment, in step S9, the temperature setting of the extruder should be adjusted according to the melting temperature range of the sheath material, generally controlled between 210°C and 280°C. The extrusion speed should match the pulling speed of the cable core to maintain the uniformity of the sheath layer. During the coating process, the thickness and quality of the sheath layer should be closely monitored to ensure that there are no bubbles, cracks, eccentricity, etc. The thickness of the sheath layer is controlled between 0.5 and 2.0 mm to provide sufficient protection.

[0033] In a preferred embodiment, in step S10, first, a withstand voltage test is performed, the cable is connected to a withstand voltage tester, the voltage is gradually increased to a specified value, such as 5000V, for 1 minute, and no breakdown phenomenon is qualified. Next, an insulation resistance test is performed, and the resistance value of the cable insulation layer is measured using an insulation resistance tester. It is required that under the specified temperature and humidity conditions, the insulation resistance value is not less than 1000M Ω·km. Finally, an aging test is performed, and the cable is placed in an aging test box to simulate the high temperature and high humidity conditions of the actual use environment, such as setting the temperature to 85°C and the humidity to 85% for 168 hours. After the aging test, the withstand voltage and insulation resistance tests are performed again, and the cable performance should meet the initial test standards.

[0034] In a preferred embodiment, in step S11, the qualified cables are cut to a specified length, and the cables are neatly coiled on a cable reel using an automatic cable coiling machine. During the coiling process, it is ensured that the cables are not twisted, damaged, or excessively bent.

[0035] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0036] 1. In the present invention, by adding an anti-corrosion additive to the cable sheath material layer, the corrosion resistance of the cable is significantly improved. The preparation process of the anti-corrosion additive involves mixing carboxyl acrylic resin with nano-tin dioxide powder, adding silane coupling agent KH-570, stirring for a long time and ultrasonic treatment, and then mixing with a variety of inorganic fillers to finally obtain an additive with excellent corrosion resistance. The application of this additive enables the cable to resist erosion by environmental factors such as acid, alkali, salt spray, and humidity, thereby extending the service life of the cable. Especially in outdoor application scenarios such as 5G communication base stations, this corrosion resistance is particularly important because it can reduce cable damage and replacement frequency caused by environmental corrosion, and reduce maintenance costs.

[0037] 2. In the present invention, the mechanical strength and tensile properties of the cable are greatly improved by weaving on the outside of the cable core and strictly controlling the sheath material coating process. Selecting the appropriate braiding angle and braiding density in the braiding step, as well as using high-strength, corrosion-resistant braiding materials, ensures that the braided layer can effectively protect the conductor core and prevent damage caused by external forces. In addition, the uniform coating and proper thickness control of the sheath layer also provide additional protection for the cable, allowing it to withstand greater mechanical stress without damage. This enhanced mechanical property not only improves the durability of the cable, but also ensures reliability and stability in complex environments, which is crucial for the stable operation of 5G communication networks. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0039] Embodiment 1:

[0040] A corrosion-resistant 5G communication cable, the 5G communication cable comprising: a cable conductor, an insulating material layer and a cable sheath material layer;

[0041] The cable conductor is a copper core;

[0042] The insulating material layer comprises 200 parts by weight of polyethylene, 25 parts by weight of antioxidant and 15 parts by weight of carbon black;

[0043] The cable sheath material layer includes 600 parts by weight of carboxyl acrylic resin, 200 parts by weight of SAN resin, 25 parts by weight of anti-corrosion additive, 2 parts by weight of lubricant, 10 parts by weight of foaming agent, 10 parts by weight of organic antimony stabilizer, 20 parts by weight of flame retardant, 10 parts by weight of reinforcing modifier and 20 parts by weight of anti-aging agent.

[0044] The production method comprises the following steps:

[0045] S1: First, prepare the raw materials for preparing the corrosion-resistant 5G communication cable, and weigh: the insulating material layer includes 200 parts by weight of polyethylene, 25 parts by weight of antioxidant and 15 parts by weight of carbon black;

[0046] 600 parts by weight of carboxyl acrylic resin, 200 parts by weight of SAN resin, 25 parts by weight of anticorrosion additive, 2 parts by weight of lubricant, 10 parts by weight of foaming agent, 10 parts by weight of organic antimony stabilizer, 20 parts by weight of flame retardant, 10 parts by weight of reinforcing modifier and 20 parts by weight of anti-aging agent;

[0047] S2: The copper core is stretched through a wire drawing machine in multiple passes to reach the required conductor diameter, and then the conductor is twisted to improve the flexibility and tensile strength of the conductor;

[0048] S3: adding the polyethylene, antioxidant and carbon black pellets weighed in step S1 into an extruder, and extruding them into a cable insulation layer after high temperature melting;

[0049] S4: Cooling the insulation layer, cooling the extruded insulation layer through a cooling water tank to ensure uniform thickness of the insulation layer;

[0050] S5: preparing a cable sheath material layer, adding polypropylene (PP) or polytetrafluoroethylene (PTFE) pellets into an extruder, and extruding them into a cable sheath layer after high-temperature melting;

[0051] S6: Cooling the jacket layer, cooling the extruded jacket layer through a cooling water tank to ensure uniform jacket layer thickness;

[0052] S7: Twisting the insulated conductors in a certain order to form a cable core;

[0053] S8: The cable core is braided outside to increase the mechanical strength and tensile strength of the cable;

[0054] S9: The braided cable core is coated with a sheath material through a coating machine to form a complete cable;

[0055] S10: Cable performance testing, including voltage resistance testing, insulation resistance testing, aging testing, etc. of finished cables to ensure that the cable performance meets the requirements of 5G communications

[0056] S11: The cables are then collected, stored and packaged, completing the entire production process of the corrosion-resistant 5G communication cable.

[0057] In step S1, the method of the anti-corrosion additive is as follows: first, take carboxyl acrylic resin and nano tin dioxide powder and mix them to a uniform state. Then, add silane coupling agent KH-570 and stir at 38 to 46 degrees Celsius for 20 to 28 hours. After stirring, cool it to room temperature and transfer it to an ice water bath for crushing. Then, perform ultrasonic treatment for 10 to 14 minutes to obtain material a.

[0058] Next, prepare an acidic composite intercalation aqueous solution, that is, disperse concentrated sulfuric acid evenly in distilled water. At the same time, place the montmorillonite in a calcining furnace and calcine it at a temperature of 750 to 850 degrees Celsius for 1 to 5 hours, followed by cooling. Soak the calcined montmorillonite in a hydrochloric acid solution for 2 to 4 hours, filter, wash and dry it, and crush it into a powder of 150 to 350 mesh. Add this powder to the acidic composite intercalation aqueous solution prepared previously, mix well, and heat the mixture to 85 to 95 degrees Celsius, and keep it warm for 1 to 3 hours.

[0059] Subsequently, material a, calcium sulfate, silicon nitride, montmorillonite powder, barium sulfate, antimony trioxide, weathered coal, seaweed powder, zinc phosphate, bentonite, zeolite powder and zirconium oxide are added to the mixture and mixed thoroughly. In a water bath of 45 to 55 degrees Celsius, ultrasonic-mechanical stirring is used to disperse for 2 to 4 hours. After standing and stratifying, the upper clear liquid is discarded, the lower reaction product is filtered and washed, and vacuum dried at 750 to 850 degrees Celsius until constant weight. The dried product is ground and screened through a 150 to 250 mesh sieve to obtain an antiseptic additive raw material A.

[0060] Finally, 10% of the total weight of nano camphor leaf fiber powder is added to the anti-corrosion agent raw material A, and the mixture is evenly mixed to obtain the final anti-corrosion agent.

[0061] In step S1, the foaming agent is azodicarbonamide.

[0062] In step S1, the flame retardant is a mixture of resorcinol bis(diphenyl phosphate), bisphenol A bis(diphenyl phosphate), tributyl tin oxide, glass fiber powder, activated clay, and aluminum hydroxide, and the mixing ratio is: resorcinol bis(diphenyl phosphate): bisphenol A bis(diphenyl phosphate): tributyl tin oxide: molybdenum hydroxide: activated clay: aluminum hydroxide = 1:2:1:1:1:3;

[0063] The anti-aging agent is one or more of tea polyphenols, phytic acid, phenolic antioxidant 1076, antioxidant 1010 or phosphite antioxidant 168

[0064] In step S1, the reinforcing modifier is a mixture of ethylene-butyl acrylate-glycidyl methacrylate terpolymer and ethylene-vinyl acetate copolymer in a weight ratio of 1-5:1-5;

[0065] The lubricant is one of calcium stearate, barium stearate, magnesium stearate and polyethylene glycol.

[0066] In step S8, first, place the insulated conductor core on the braiding machine, and select the appropriate braiding angle and braiding density according to the design requirements of the cable. The braiding angle is usually set between 45° and 90° to balance the softness and strength of the cable. The braiding density is determined according to the use environment of the cable, and generally the number of braided wires per meter length is selected between 10 and 30. During the braiding process, ensure that the braided layer is close to the conductor core without looseness and blistering. Braiding materials usually select high-strength, corrosion-resistant metals or synthetic fibers. The braiding speed should be adjusted according to the material properties and equipment performance to maintain the stability and efficiency of the braiding process. During the entire braiding process, the operator needs to regularly check the braiding quality to ensure the uniformity and integrity of the cable braiding layer.

[0067] In step S9, the temperature setting of the extruder should be adjusted according to the melting temperature range of the sheath material, generally controlled between 210°C and 280°C. The extrusion speed should match the pulling speed of the cable core to maintain the uniformity of the sheath layer. During the coating process, the thickness and quality of the sheath layer should be closely monitored to ensure that there are no bubbles, cracks, eccentricity, etc. The thickness of the sheath layer is controlled between 0.5 and 2.0 mm to provide adequate protection.

[0068] In step S10, first, a withstand voltage test is performed, the cable is connected to a withstand voltage tester, and the voltage is gradually increased to a specified value, such as 5000V, for 1 minute. If there is no breakdown, it is qualified. Next, an insulation resistance test is performed, and the insulation resistance tester is used to measure the resistance value of the cable insulation layer. It is required that under the specified temperature and humidity conditions, the insulation resistance value is not less than 1000MΩ·km. Finally, an aging test is performed, and the cable is placed in an aging test chamber to simulate the high temperature and high humidity conditions of the actual use environment, such as setting the temperature to 85°C and the humidity to 85% for 168 hours. After the aging test, the withstand voltage and insulation resistance tests are performed again, and the cable performance should meet the initial test standards.

[0069] In step S11, the qualified cables are cut to the specified length, and the cables are neatly coiled on the cable drum using an automatic cable coiling machine. During the coiling process, it is necessary to ensure that the cables are not twisted, damaged, or excessively bent.

[0070] In the present invention, by adding an anti-corrosion additive to the cable sheath material layer, the corrosion resistance of the cable is significantly improved. The preparation process of the anti-corrosion additive involves mixing a carboxyl acrylic resin with a nano-tin dioxide powder, adding a silane coupling agent KH-570, stirring for a long time and ultrasonic treatment, and then mixing with a variety of inorganic fillers to finally obtain an additive with excellent corrosion resistance. The application of this additive enables the cable to resist erosion by environmental factors such as acid, alkali, salt spray, and humidity, thereby extending the service life of the cable. Especially in outdoor application scenarios such as 5G communication base stations, this corrosion resistance is particularly important because it can reduce cable damage and replacement frequency caused by environmental corrosion, and reduce maintenance costs.

[0071] In the present invention, the mechanical strength and tensile strength of the cable are greatly improved by weaving the outside of the cable core and strictly controlling the sheath material coating process. Selecting the appropriate braiding angle and braiding density in the braiding step, and using high-strength, corrosion-resistant braiding materials, ensure that the braided layer can effectively protect the conductor core and prevent damage caused by external forces. In addition, the uniform coating and proper thickness control of the sheath layer also provide additional protection for the cable, enabling it to withstand greater mechanical stress without damage. This enhanced mechanical property not only improves the durability of the cable, but also ensures reliability and stability in complex environments, which is crucial for the stable operation of 5G communication networks.

[0072] Embodiment 2:

[0073] A corrosion-resistant 5G communication cable, the 5G communication cable comprising: a cable conductor, an insulating material layer and a cable sheath material layer;

[0074] The cable conductor is a copper core;

[0075] The insulating material layer comprises 400 parts by weight of polyethylene, 35 parts by weight of antioxidant and 25 parts by weight of carbon black;

[0076] The cable sheath material layer includes 800 parts by weight of carboxyl acrylic resin, 400 parts by weight of SAN resin, 35 parts by weight of anti-corrosion additive, 5 parts by weight of lubricant, 20 parts by weight of foaming agent, 18 parts by weight of organic antimony stabilizer, 30 parts by weight of flame retardant, 20 parts by weight of reinforcing modifier and 25 parts by weight of anti-aging agent.

[0077] The production method comprises the following steps:

[0078] S 1: First, prepare the raw materials for preparing the corrosion-resistant 5G communication cable, and weigh: 400 parts by weight of polyethylene, 35 parts by weight of antioxidant and 25 parts by weight of carbon black;

[0079] 800 parts by weight of carboxyl acrylic resin, 400 parts by weight of SAN resin, 35 parts by weight of anticorrosion additive, 5 parts by weight of lubricant, 20 parts by weight of foaming agent, 18 parts by weight of organic antimony stabilizer, 30 parts by weight of flame retardant, 20 parts by weight of reinforcing modifier and 25 parts by weight of anti-aging agent;

[0080] S2: The copper core is stretched through a wire drawing machine in multiple passes to reach the required conductor diameter, and then the conductor is twisted to improve the flexibility and tensile strength of the conductor;

[0081] S3: adding the polyethylene, antioxidant and carbon black pellets weighed in step S1 into an extruder, and extruding them into a cable insulation layer after high temperature melting;

[0082] S4: Cooling the insulation layer, cooling the extruded insulation layer through a cooling water tank to ensure uniform thickness of the insulation layer;

[0083] S5: preparing a cable sheath material layer, adding polypropylene (PP) or polytetrafluoroethylene (PTFE) pellets into an extruder, and extruding them into a cable sheath layer after high-temperature melting;

[0084] S6: Cooling the jacket layer, cooling the extruded jacket layer through a cooling water tank to ensure uniform jacket layer thickness;

[0085] S7: Twisting the insulated conductors in a certain order to form a cable core;

[0086] S8: The cable core is braided outside to increase the mechanical strength and tensile strength of the cable;

[0087] S9: The braided cable core is coated with a sheath material through a coating machine to form a complete cable;

[0088] S 10: Cable performance testing, including voltage resistance testing, insulation resistance testing, aging testing, etc. of finished cables to ensure that the cable performance meets the requirements of 5G communications

[0089] S11: The cables are then collected, stored and packaged, completing the entire production process of the corrosion-resistant 5G communication cable.

[0090] In step S1, the method of the anti-corrosion additive is as follows: first, take carboxyl acrylic resin and nano tin dioxide powder and mix them to a uniform state. Then, add silane coupling agent KH-570 and stir at 38 to 46 degrees Celsius for 20 to 28 hours. After stirring, cool it to room temperature and transfer it to an ice water bath for crushing. Then, perform ultrasonic treatment for 10 to 14 minutes to obtain material a.

[0091] Next, prepare an acidic composite intercalation aqueous solution, that is, disperse concentrated sulfuric acid evenly in distilled water. At the same time, place the montmorillonite in a calcining furnace and calcine it at a temperature of 750 to 850 degrees Celsius for 1 to 5 hours, followed by cooling. Soak the calcined montmorillonite in a hydrochloric acid solution for 2 to 4 hours, filter, wash and dry it, and crush it into a powder of 150 to 350 mesh. Add this powder to the acidic composite intercalation aqueous solution prepared previously, mix well, and heat the mixture to 85 to 95 degrees Celsius, and keep it warm for 1 to 3 hours.

[0092] Subsequently, material a, calcium sulfate, silicon nitride, montmorillonite powder, barium sulfate, antimony trioxide, weathered coal, seaweed powder, zinc phosphate, bentonite, zeolite powder and zirconium oxide are added to the mixture and mixed thoroughly. In a water bath of 45 to 55 degrees Celsius, ultrasonic-mechanical stirring is used to disperse for 2 to 4 hours. After standing and stratifying, the upper clear liquid is discarded, the lower reaction product is filtered and washed, and vacuum dried at 750 to 850 degrees Celsius until constant weight. The dried product is ground and screened through a 150 to 250 mesh sieve to obtain an antiseptic additive raw material A.

[0093] Finally, 10% of the total weight of nano camphor leaf fiber powder is added to the anti-corrosion agent raw material A, and the mixture is evenly mixed to obtain the final anti-corrosion agent.

[0094] In step S1, the foaming agent is azodicarbonamide.

[0095] In step S1, the flame retardant is a mixture of resorcinol bis(diphenyl phosphate), bisphenol A bis(diphenyl phosphate), tributyl tin oxide, glass fiber powder, activated clay, and aluminum hydroxide, and the mixing ratio is: resorcinol bis(diphenyl phosphate): bisphenol A bis(diphenyl phosphate): tributyl tin oxide: molybdenum hydroxide: activated clay: aluminum hydroxide = 1:2:1:1:1:3;

[0096] The anti-aging agent is one or more of tea polyphenols, phytic acid, phenolic antioxidant 1076, antioxidant 1010 or phosphite antioxidant 168

[0097] In step S1, the reinforcing modifier is a mixture of ethylene-butyl acrylate-glycidyl methacrylate terpolymer and ethylene-vinyl acetate copolymer in a weight ratio of 1-5:1-5;

[0098] The lubricant is one of calcium stearate, barium stearate, magnesium stearate and polyethylene glycol.

[0099] In step S8, first, place the insulated conductor core on the braiding machine, and select the appropriate braiding angle and braiding density according to the design requirements of the cable. The braiding angle is usually set between 45° and 90° to balance the softness and strength of the cable. The braiding density is determined according to the use environment of the cable, and generally the number of braided wires per meter length is selected between 10 and 30. During the braiding process, ensure that the braided layer is close to the conductor core without looseness and blistering. Braiding materials usually select high-strength, corrosion-resistant metals or synthetic fibers. The braiding speed should be adjusted according to the material properties and equipment performance to maintain the stability and efficiency of the braiding process. During the entire braiding process, the operator needs to regularly check the braiding quality to ensure the uniformity and integrity of the cable braiding layer.

[0100] In step S9, the temperature setting of the extruder should be adjusted according to the melting temperature range of the sheath material, generally controlled between 210°C and 280°C. The extrusion speed should match the pulling speed of the cable core to maintain the uniformity of the sheath layer. During the coating process, the thickness and quality of the sheath layer should be closely monitored to ensure that there are no bubbles, cracks, eccentricity, etc. The thickness of the sheath layer is controlled between 0.5 and 2.0 mm to provide adequate protection.

[0101] In step S10, first, a withstand voltage test is performed, the cable is connected to a withstand voltage tester, and the voltage is gradually increased to a specified value, such as 5000V, for 1 minute. If there is no breakdown, it is qualified. Next, an insulation resistance test is performed, and the insulation resistance tester is used to measure the resistance value of the cable insulation layer. It is required that under the specified temperature and humidity conditions, the insulation resistance value is not less than 1000MΩ·km. Finally, an aging test is performed, and the cable is placed in an aging test chamber to simulate the high temperature and high humidity conditions of the actual use environment, such as setting the temperature to 85°C and the humidity to 85% for 168 hours. After the aging test, the withstand voltage and insulation resistance tests are performed again, and the cable performance should meet the initial test standards.

[0102] In step S11, the qualified cables are cut to the specified length, and the cables are neatly coiled on the cable drum using an automatic cable coiling machine. During the coiling process, it is necessary to ensure that the cables are not twisted, damaged, or excessively bent.

[0103] In the present invention, by adding an anti-corrosion additive to the cable sheath material layer, the corrosion resistance of the cable is significantly improved. The preparation process of the anti-corrosion additive involves mixing a carboxyl acrylic resin with a nano-tin dioxide powder, adding a silane coupling agent KH-570, stirring for a long time and ultrasonic treatment, and then mixing with a variety of inorganic fillers to finally obtain an additive with excellent corrosion resistance. The application of this additive enables the cable to resist erosion by environmental factors such as acid, alkali, salt spray, and humidity, thereby extending the service life of the cable. Especially in outdoor application scenarios such as 5G communication base stations, this corrosion resistance is particularly important because it can reduce cable damage and replacement frequency caused by environmental corrosion, and reduce maintenance costs.

[0104] In the present invention, the mechanical strength and tensile strength of the cable are greatly improved by weaving the outside of the cable core and strictly controlling the sheath material coating process. Selecting the appropriate braiding angle and braiding density in the braiding step, and using high-strength, corrosion-resistant braiding materials, ensure that the braided layer can effectively protect the conductor core and prevent damage caused by external forces. In addition, the uniform coating and proper thickness control of the sheath layer also provide additional protection for the cable, enabling it to withstand greater mechanical stress without damage. This enhanced mechanical property not only improves the durability of the cable, but also ensures reliability and stability in complex environments, which is crucial for the stable operation of 5G communication networks.

[0105] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprises" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0106] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A corrosion-resistant 5G communication cable, Features: The 5G communication cable comprises: a cable conductor, an insulating material layer and a cable sheath material layer; The cable conductor is a copper core; The insulating material layer comprises 200 to 400 parts by weight of polyethylene, 25 to 35 parts by weight of antioxidant and 15 to 25 parts by weight of carbon black; The cable sheath material layer comprises 600-800 parts by weight of carboxyl acrylic resin, 200-400 parts by weight of SAN resin, 25-35 parts by weight of anticorrosion additive, 2-5 parts by weight of lubricant, 10-20 parts by weight of foaming agent, 10-18 parts by weight of organic antimony stabilizer, 20-30 parts by weight of flame retardant, 10-20 parts by weight of reinforcing modifier and 20-25 parts by weight of anti-aging agent.

2. A method for producing a corrosion-resistant 5G communication cable as claimed in claim 1, Features: The production method comprises the following steps: S1: First, prepare the raw materials for preparing the corrosion-resistant 5G communication cable, and weigh: 200-400 parts by weight of polyethylene, 25-35 parts by weight of antioxidant and 15-25 parts by weight of carbon black; 600-800 parts by weight of carboxyl acrylic resin, 200-400 parts by weight of SAN resin, 25-35 parts by weight of anticorrosion additive, 2-5 parts by weight of lubricant, 10-20 parts by weight of foaming agent, 10-18 parts by weight of organic antimony stabilizer, 20-30 parts by weight of flame retardant, 10-20 parts by weight of reinforcing modifier and 20-25 parts by weight of anti-aging agent; S2: The copper core is stretched through a wire drawing machine in multiple passes to reach the required conductor diameter, and then the conductor is twisted to improve the flexibility and tensile strength of the conductor; S3: adding the polyethylene, antioxidant and carbon black pellets weighed in step S1 into an extruder, and extruding them into a cable insulation layer after high temperature melting; S4: Cooling the insulation layer, cooling the extruded insulation layer through a cooling water tank to ensure uniform thickness of the insulation layer; S5: preparing a cable sheath material layer, adding polypropylene (PP) or polytetrafluoroethylene (PTFE) pellets into an extruder, and extruding them into a cable sheath layer after high-temperature melting; S6: Cooling the jacket layer, cooling the extruded jacket layer through a cooling water tank to ensure uniform jacket layer thickness; S7: Twisting the insulated conductors in a certain order to form a cable core; S8: The cable core is braided outside to increase the mechanical strength and tensile strength of the cable; S9: The braided cable core is coated with a sheath material through a coating machine to form a complete cable; S10: Cable performance testing, including voltage resistance testing, insulation resistance testing, aging testing, etc. of finished cables to ensure that the cable performance meets the requirements of 5G communications S11: The cables are then collected, stored and packaged, completing the entire production process of the corrosion-resistant 5G communication cable.

3. A method for producing a corrosion-resistant 5G communication cable as claimed in claim 2, Features: In step S1, the method of preparing the anti-corrosion additive is as follows: first, taking carboxyl acrylic resin and nano-tin dioxide powder, mixing them until they are uniform; then, adding silane coupling agent KH-570, stirring at 38 to 46 degrees Celsius for 20 to 28 hours; after the stirring is completed, cooling it to room temperature, and transferring it to an ice water bath for crushing; then, performing ultrasonic treatment for 10 to 14 minutes to obtain material a; Next, an acidic composite intercalation aqueous solution is prepared, that is, concentrated sulfuric acid is uniformly dispersed in distilled water; at the same time, montmorillonite is placed in a calcining furnace, calcined at a temperature of 750 to 850 degrees Celsius for 1 to 5 hours, and then cooled; the calcined montmorillonite is placed in a hydrochloric acid solution and soaked for 2 to 4 hours, filtered, washed and dried, and then crushed into a powder of 150 to 350 mesh; the powder is added to the acidic composite intercalation aqueous solution prepared previously, mixed evenly, and the mixture is heated to 85 to 95 degrees Celsius and maintained for 1 to 3 hours of insulation treatment; Subsequently, material a, calcium sulfate, silicon nitride, montmorillonite powder, barium sulfate, antimony trioxide, weathered coal, seaweed powder, zinc phosphate, bentonite, zeolite powder and zirconium oxide are added to the mixture and mixed thoroughly; the mixture is dispersed in a water bath at 45 to 55 degrees Celsius by ultrasonic-mechanical stirring for 2 to 4 hours; after standing and stratifying, the upper clear liquid is discarded, the lower reaction product is filtered and washed, and vacuum dried at 750 to 850 degrees Celsius until constant weight is reached; the dried product is ground and screened through a 150 to 250 mesh sieve to obtain a preservative additive raw material A; Finally, 10% of the total weight of nano camphor leaf fiber powder is added to the anti-corrosion agent raw material A, and the mixture is evenly mixed to obtain the final anti-corrosion agent.

4. A method for producing a corrosion-resistant 5G communication cable as claimed in claim 2, Features: In the step S1, the foaming agent is azodicarbonamide.

5. A method for producing a corrosion-resistant 5G communication cable as claimed in claim 2, Features: In step S1, the flame retardant is a mixture of resorcinol bis(diphenyl phosphate), bisphenol A bis(diphenyl phosphate), tributyl tin oxide, glass fiber powder, activated clay, and aluminum hydroxide, and the mixing ratio is: resorcinol bis(diphenyl phosphate): bisphenol A bis(diphenyl phosphate): tributyl tin oxide: molybdenum hydroxide: activated clay: aluminum hydroxide = 1:2:1:1:1:3; The anti-aging agent is one or more of tea polyphenols, phytic acid, phenolic antioxidant 1076, antioxidant 1010 or phosphite antioxidant 168.

6. A method for producing a corrosion-resistant 5G communication cable as claimed in claim 2, Features: In the step S1, the reinforcing modifier is a mixture of ethylene-butyl acrylate-glycidyl methacrylate terpolymer and ethylene-vinyl acetate copolymer in a weight ratio of 1-5:1-5; The lubricant is one of calcium stearate, barium stearate, magnesium stearate and polyethylene glycol.

7. A method for producing a corrosion-resistant 5G communication cable as claimed in claim 2, Features: In the step S8, first, the insulated conductor core is placed on the braiding machine, and a suitable braiding angle and braiding density are selected according to the design requirements of the cable; the braiding angle is usually set between 45° and 90° to balance the softness and strength of the cable; the braiding density is determined according to the use environment of the cable, and generally the number of braided wires per meter length is selected between 10 and 30; during the braiding process, it is necessary to ensure that the braided layer is close to the conductor core without looseness and blistering; the braiding material is usually selected from high-strength, corrosion-resistant metals or synthetic fibers; the braiding speed should be adjusted according to the material properties and equipment performance to maintain the stability and efficiency of the braiding process; during the entire braiding process, the operator needs to regularly check the braiding quality to ensure the uniformity and integrity of the cable braiding layer.

8. A method for producing a corrosion-resistant 5G communication cable as claimed in claim 2, Features: In the step S9, the temperature setting of the extruder should be adjusted according to the melting temperature range of the sheath material, generally controlled between 210°C and 280°C; the extrusion speed should match the pulling speed of the cable core to maintain the uniformity of the sheath layer; during the coating process, the thickness and quality of the sheath layer should be closely monitored to ensure that there are no bubbles, cracks, eccentricity, etc.; The thickness of the sheath layer is controlled between 0.5 and 2.0 mm to provide adequate protection.

9. A method for producing a corrosion-resistant 5G communication cable as claimed in claim 2, Features: In the step S10, first, a withstand voltage test is performed, the cable is connected to a withstand voltage tester, the voltage is gradually increased to a specified value, such as 5000V, for 1 minute, and no breakdown phenomenon is qualified; then, an insulation resistance test is performed, the insulation resistance value of the cable insulation layer is measured using an insulation resistance tester, and the insulation resistance value is required to be not less than 1000MΩ·km under specified temperature and humidity conditions; finally, an aging test is performed, the cable is placed in an aging test box, and the high temperature and high humidity conditions of the actual use environment are simulated, such as setting the temperature to 85°C and the humidity to 85% for 168 hours; After the aging test, the withstand voltage and insulation resistance tests are carried out again, and the cable performance should meet the initial test standards.

10. A method for producing a corrosion-resistant 5G communication cable according to claim 2, Features: In the step S11, the qualified cables are cut into a specified length, and the cables are neatly coiled on a cable drum using an automatic cable coiling machine; During coiling, ensure that the cable is free from twists, damage and excessive bends.